Hudson's building and engineering contracts : including the duties and liabilities of architects, engineers and surveyors - Hudson, Alfred A.; Wallace, I. N. Duncan (London : Sweet & Maxwell, 1970)
This book provides insight into the Hudson's activities, as it explained majority of the more substantial building and engineering projects in the United Kingdom are designed by professional adviser of the employer, and are usually supervised and administered on the employer's behalf.
First ed. has titled: The law of building and engineering contracts; 2d-4th ed. entitled: The law of building, engineering and ship building contracts; 5th-7th ed. entitled: The law of building and engineering contracts; and 8th-10th ed. entitled: Hudson's Building and engineering contracts.
Kept up to date by supplements.
Includes bibliographical footnotes and index.
ii 17/01/2019
Loans
Keywords: Construction contracts; Engineering contracts; Engineering law; Architects; Malpractice